THE PERFORMANCE OF PACIFIC WHITE SHRIMP INFECTED BY Vibrio harveyi AFTER MANGROVE LEAF EXTRACT SUPPLEMENTATION - Linayati - Linayati; Maghfiroh Maghfiroh; Adhitya Wisnu Prasetyo; M. Zulkham Yahya (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2023)
This research investigated the advantages and determined the optimal dosage of mangrove leaf supplementation to enhance growth and disease resistance in shrimp. PL-20 Pacific White Shrimp were given different doses of mangrove leaf extract added to their feed: 0 ppm/500 g (A), 225 ppm/500 g (B), 250 ppm/500 g (C), and 275 ppm/ 500 g (D), over a 30-day period. This experimental research was conducted using a completely randomized design with four treatments and three replications each. Several parameters were observed: growth, feed conversion ratio (FCR), energy protein productivity (EPP), and subsequent exposure to Vibrio harveyi to assess survival rate (SR). The obtained data underwent ANOVA analysis, which results demonstrated significant influence in shrimp growth, with the most notable improvement observed in treatment D. Treatment D also exhibited the highest SR value following the challenge test. Throughout the study, water quality parameters remained within the suitable range for fostering shrimp growth